The Outcome of Critically Ill COVID-19 Patients Is Linked to Thromboinflammation Dominated by the Kallikrein/Kinin System - Lipcsey, Miklós; Persson, Barbro; Eriksson, Oskar; Blom, Anna M.; Fromell, Karin; Hultström, Michael; Huber-Lang, Markus; Ekdahl, Kristina N.; Frithiof, Robert; Nilsson, Bo (Frontiers in Immunology, 2021)
An important manifestation of severe COVID-19 is the ARDS-like lung injury that is associated with vascular endothelialitis, thrombosis and angiogenesis. The intravascular innate immune system (IIIS), including the complement, contact, coagulation, and fibrinolysis systems, which is crucial for recognizing and eliminating microorganisms and debris in the body, is likely to be involved in the pathogenesis of COVID-19 ARDS. Biomarkers for IIIS activation was studied in the first 66 patients with COVID-19 admitted to the ICU in Uppsala University Hospital, both cross-sectionally on day 1 and in 19 patients longitudinally for up to a month, in a prospective study. IIIS analyses were compared with biochemical parameters and clinical outcome and survival. Blood cascade systems activation leading to an overreactive conjunct thromboinflammation was demonstrated, reflected in consumption of individual cascade system components e.g. FXII, prekallikrein and high molecular weight kininogen and in increased levels of activation products e.g., C4d, C3a, C3d,g, sC5b-9, TAT, and D-dimer. Strong associations were found between the blood cascade systems and organ damage, illness severity scores and survival. We show that critically ill COVID-19 patients display a conjunct activation of the IIIS that is linked to organ damage of the lung, heart, kidneys and death. We present evidence that the complement and in particular the kallikrein/kinin system is strongly activated and that both systems are prognostic markers of the outcome of the patients suggesting their role in driving the inflammation. Already licensed kallikrein/kinin inhibitors are potential drugs for treatment of critically ill patients with COVID-19.